2002
DOI: 10.1016/s1097-2765(02)00701-3
|View full text |Cite
|
Sign up to set email alerts
|

NFATc2-Mediated Repression of Cyclin-Dependent Kinase 4 Expression

Abstract: to be distinct from the other NFAT isoforms (Lopez-2 Department of Adult Oncology Rodriguez et al., 1999; Miyakawa et al., 1999; Trama et The Dana-Farber Cancer Institute al., 2000). Harvard Medical School It has been extensively demonstrated that NFATc1, Boston, Massachusetts 02115 c2, and c3 require the continued activation of calcineurin 3 AMC Cancer Research Center and (Loh et al., 1996) and AP-1 elements (Macian et al., Donald Monk Cancer Research Foundation 2001) in order to regulate the production of nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
177
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(192 citation statements)
references
References 41 publications
13
177
1
1
Order By: Relevance
“…Cyclophilin A is also known to promote calcineurindependent G 1 -S transition by up-regulating cyclin D1 expression and Cdk4 activity in late G 1 phase (21)(22)(23). We confirmed up-regulation of both cyclin D1 and Cdk4 expression by cyclophilin A (10 ng/mL) treatment 60 minutes after exposure in synchronized H1299 cells; however, in the cyclophilin Amediated G 1 -S transition, there was no significant change in p21 WAF1 expression levels (Fig.…”
Section: Fhit Inhibits Cyclophilin a -Mediated Calcineurin Activity Asupporting
confidence: 61%
“…Cyclophilin A is also known to promote calcineurindependent G 1 -S transition by up-regulating cyclin D1 expression and Cdk4 activity in late G 1 phase (21)(22)(23). We confirmed up-regulation of both cyclin D1 and Cdk4 expression by cyclophilin A (10 ng/mL) treatment 60 minutes after exposure in synchronized H1299 cells; however, in the cyclophilin Amediated G 1 -S transition, there was no significant change in p21 WAF1 expression levels (Fig.…”
Section: Fhit Inhibits Cyclophilin a -Mediated Calcineurin Activity Asupporting
confidence: 61%
“…[8][9][10][11] It has been shown that NFAT1 directly binds specific sites at the CDK4 and Cyclin A2 promoters and negatively regulates the expression of both genes, suggesting an inhibitory role for NFAT1 in cell cycle progression. 8,9 However, the role of NFAT1 protein in cell cycle regulation of B lymphocytes has not been fully addressed. Here, we show that NFAT1 deficiency causes Cyclin E1 and E2 overexpression at the mRNA level in B cells, which is followed by increased protein levels (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Besides the canonical cytokines and cell surface markers regulated by NFAT transcription factors, several reports have shown that NFAT proteins control the activity of promoter and enhancer regions of many other inducible genes, such as FasL, Cox-2, and Vegf. [5][6][7] NFAT transcription factors have also been shown to regulate the expression of cell cycle-related genes, such as Cdk-4, Cyclin A2, C-Myc and p15 INK4b , [8][9][10][11] indicating a central role for this family of transcription factors in cellular proliferation and tumorigenesis. Indeed, different NFAT family members have been related to tumor-associated processes, such as growth factor independency, apoptosis, angiogenesis, and invasiveness.…”
Section: Introductionmentioning
confidence: 99%
“…NFAT1, NFAT2, NFAT3 and NFAT4 have been first identified as T-cell transcription factors, whereas NFAT5 has been involved in the cellular response to osmotic stress (Macian, 2005;Burg et al, 2007;Mancini and Toker, 2009;Muller and Rao, 2010). It is now well documented that NFAT proteins are also present in non-immune cells and regulate a variety of signaling pathways involved in cell growth and development (Baksh et al, 2002;Chuvpilo et al, 2002;Mancini and Toker, 2009;Muller and Rao, 2010). Importantly, members of the NFAT family, in particular NFAT5, have recently been involved in the migratory capacity of breast cancer cells (Jauliac et al, 2002;Ayers et al, 2004;Yoeli-Lerner et al, 2005;Mancini and Toker, 2009;Fougere et al, 2010;Muller and Rao, 2010).…”
Section: Introductionmentioning
confidence: 99%